The Choice of Curriculum for Refugee Children: An Ethiopian Case - Demissie, Eyueil Abate; Boru, Ambissa Kenea (Indonesian Journal of Curriculum and Educational Technology Studies, 2021)
This research is conducted to investigate the contrasting theories in the curriculum of choice for educating refugee children and the perception of participants in related to the implemented curriculum for educating primary school children in Jewi refugee camp. Interview, document analysis, and observation are the data collecting tools used in this research. The research is a qualitative single case study. Students, teachers, school leaders, parents, and concerned officials from governmental and non-governmental institutions took part in this study. The results of this research noted that the curriculum implemented in the education for refugee children has a gap in considering previous educational background of refugee children, the impact of the crisis on them, and their future life in home, host, or third country. Adopting the host country curriculum is seen to be subjected for frequent students and parental complain especially on history, geography, language, and civics subjects. With this understanding adopting a negotiated curriculum between home and host country is identified to be relevant. Abstrak Penelitian ini bertujuan untuk mengetahui perbedaan teoretis dalam pilihan kurikulum yang diperuntukkan bagi anak-anak pengungsi dan persepsi partisipan terkait dengan implementasi kurikulum, terutama di sekolah dasar di kamp pengungsian Jewi. Penggalian data menggunakan wawancara, penelusuran dokumen, dan observasi. Penelitian ini merupakan penelitian studi kasus tunggal yang melibatkan siswa, guru, pimpinan sekolah, orang tua, dan pejabat pemerintah maupun non-pemerintah. Hasil penelitian menunjukkan bahwa penerapan kurikulum untuk anak-anak di pengungsian terdapat kesenjangan, antara lain terkait dengan latar Pendidikan mereka, imbas krisis pada kehidupan mereka, termasuk tempat tinggal mereka yang akan datang, baik tempat tinggal sendiri maupun di negara lain. Mengadopsi kurikulum yang berasal dari negara tempat anak-anak pengungsi tinggal tampaknya merupakan pilihan dari banyak anak dan juga menjadi sasaran kritik, terutama terkait materi sejarah, geografi, Bahasa, dan kewarganegaraan. Oleh karena itu, mengadopsi kurikulum yang mampu menegosiasikan antara materi dari negara asal dan negara tempat tinggal tampak relevan dipilih.